Revealing the capability of the European hake to cope with micro-litter environmental exposure and its inferred potential health impact in the NW Mediterranean Sea. (April 2023) - Muns-Pujadas, Laura; Dallarés, Sara; Constenla, Maria; Padrós, Francesc; Carreras-Colom, Ester; Grelaud, Michaël; Carrassón, Maite; Soler-Membrives, Anna
Abstract: Prevalence, abundance, concentration, size and composition of anthropogenic items (AIs) (synthetic and non-synthetic) ingested by Merluccius merluccius juvenile specimens and from near-bottom water samples from different localities off the Catalan coast (NW Mediterranean), were characterized. The potential effect of AIs on fish condition was assessed through different health indicators. Virtually all AIs found in fish and near-bottom water samples were fibres. A mean of 0.85 fibres/m 3 from the surrounding water was observed. Fish ingested a mean of 1.39 (SD = 1.39) items/individual. Cellulosic fibres were predominant (77.8% of samples), except for Barcelona. No differences in ingested AIs abundance and composition off Barcelona between 2007 and 2019 were found. Small AIs from the environment matched ingested AIs composition. Hakes did not ingest large fibres despite being present in the environment, probably due to their feeding behaviour. No adverse health effects or parasites aggregations were detected to be potentially related to AIs ingestion. Graphical abstract: Image 1 Highlights: Anthropogenic items (AIs) from hakes and surrounding water first time quantified. Hakes avoid uptaking large AIs from the surrounding environment. Small AIs ingested by fish match with those present in the near-bottom environment. Cellulose is the most abundant polymer in hakes and in the environment. No apparent adverse fish health effects due to AIs were detected.